A tve curriculum framework for sustainability literacy - Chidozie, Chinedu Caleb (2019)
Existing curriculum frameworks for sustainability literacy emphasize the importance of curriculum reorientation but do not take cognisance of the essential Education for Sustainable Development (ESD) components that are needed for such curricular reorientation. To develop sustainability literate citizens and workers, ESD must become an integral part of the learning experiences provided in TVE teacher education programs. Therefore, this study sought to develop a curriculum framework for sustainability literacy. The study was carried out in three phases using a triangulation design. Phase one explored the extent to which ESD is reflected in four TVE teacher training programs in Malaysia using Qualitative Document Analysis (QDA) approach. The study in phase two explored the perspectives of 15 ESD experts about the important curriculum components required for sustainability literacy in TVE using a modified Delphi method. In phase three a survey of 116 TVE educators was carried out to validate the identified curriculum framework components in terms of their utility value and feasibility for implementation in TVE. Findings from the QDA revealed that ESD was essentially minimal, as only minute depictions of the concept were reflected across the TVE programs. Four curriculum components for sustainability literacy in TVE were identified from the modified Delphi. These identified framework components reflect the sustainability knowledge, skills and attributes required to develop sustainability competent vocational teachers. Findings from phase three reveals that TVE educators consider all the identified framework components and dimensions important for inclusion in the existing TVE curriculum. These components provide opportunities to develop vocational teachers of the future, who possess the requisite skills to facilitate teaching and learning on sustainability issues and concepts. The framework also proposes using a range of active learning pedagogical approaches to develop pre-service teacher’s competencies on sustainability literacy.